2020
DOI: 10.1016/j.bbapap.2020.140531
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional d-aspartate metabolism in BTBR mouse model of idiopathic autism

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 91 publications
1
17
0
Order By: Relevance
“…This novel finding was quite inconsistent with the traditional theory that L-aspartate being mainly produced in the liver. 42,43 In addition to L-aspartate, we also observed that A. muciniphila treatment elevated the levels of SCFAs in liver including propionate and acetate, which have beneficial metabolic effects in curbing obesity and MAFLD. 44,45 The elevated metabolites may separately or together underlie the therapeutic effect of A. muciniphila in MAFLD.…”
Section: Discussionmentioning
confidence: 67%
“…This novel finding was quite inconsistent with the traditional theory that L-aspartate being mainly produced in the liver. 42,43 In addition to L-aspartate, we also observed that A. muciniphila treatment elevated the levels of SCFAs in liver including propionate and acetate, which have beneficial metabolic effects in curbing obesity and MAFLD. 44,45 The elevated metabolites may separately or together underlie the therapeutic effect of A. muciniphila in MAFLD.…”
Section: Discussionmentioning
confidence: 67%
“…Furthermore, A. muciniphila treatment increased the expression level of the L-aspartate transporter in the ileum and liver, suggesting that A. muciniphila plays an important role in regulating L-aspartate transportation. This novel finding was quite unfamiliar with the traditional theory of L-aspartate being mainly produced in the liver (Nuzzo et al, 2020;Leng et al, 2014). Moreover, a negative correlation was observed between the L-aspartate level and the hepatic TG level, suggesting that A. muciniphila ameliorated NAFLD in mice may be closely related to the increased levels of L-aspartate.…”
Section: Discussionmentioning
confidence: 82%
“…Given that NMDARs regulate neuron development, maturation, and migration [77][78][79][80], we argue that D-Asp is a candidate signaling molecule involved in neurodevelopmental processes. Notably, a recent study revealed a severe reduction of Ddo gene expression accompanied by an increase of D-Asp levels in the brain of BTBR mice, which is a widely accredited animal model of idiopathic autism [14]. Furthermore, in an attempt to understand the biological meaning of the elevated levels of D-Asp during brain development, a Ddo knock-in mouse model with complete depletion of this D-amino acid has been generated [22].…”
Section: Animal Models With Altered D-aspartate Metabolismmentioning
confidence: 99%
“…Conversely, the concentration of this amino acid is low in the endocrine glands during gestational phases and progressively increases during postnatal life [12]. Pharmacologically, D-Asp can modulate glutamatergic NMDAR-mediated transmission and functions, and dysregulation of its metabolism occurs in the brain of schizophrenia patients and in an animal model of autism spectrum disorders [13][14][15].…”
Section: Introductionmentioning
confidence: 99%